Synthesis and Voltammetric Determination of Pb(II) Using a ZIF-8-Based Electrode - Dinh Quang Khieu; Mai Thi Thanh; Tran Vinh Thien; Nguyen Hai Phong; Duc Hoang Van; Pham Dinh Du; Nguyen Phi Hung (Journal of Chemistry)
Zeolite imidazole framework-8 (ZIF-8) was prepared by the hydrothermal process. The obtained ZIF-8 was a characteristic of X-ray-diffraction (XRD), transmission electron microscope (TEM), thermal gravity-differential thermal analysis (TG-DTA), and dynamic light scattering (DLS). The obtained ZIF-8 possessed large specific area and was highly dispersed. Its morphology consisted of nanospherical particles with 30–50 nm in diameter. Chemical stability of ZIF-8 in different conditions was studied. The ZIF-8 was used as an electrode modifier for the determination of trace levels of lead. The parameters including solvents and solution pH were investigated. The repeatability, reproducibility, accuracy, linear range, limit of detection, and limit of quantitation were also addressed. The results showed that ZIF-8 is a potential electrode modifier for differential pulse anodic stripping method to determine Pb(II) in aqueous solution.